Pediatric Scaphoid Nonunions: A Case Series, Review of the Literature, and Evidence-Based Guidelines - Oestreich, Kerstin; Jacomel, Tatiana Umata Yoko; Hassan, Sami; Horwitz, Maxim David; Lindau, Tommy Roger (Journal of Wrist Surgery, 2020)
Background Scaphoid fractures represent less than 3% of hand and wrist fractures in the pediatric population. Nonunions are very rare. We present a case series (n = 18) of nonunions in skeletally immature children and adolescents. We further present a review of the literature on pediatric scaphoid nonunions.Materials and Methods We reviewed the literature by searching the main databases on pediatric scaphoid nonunions, but to identify factors that lead to nonunion, we also searched for databases on scaphoid fractures. Seventy articles were found for the period between 1961 and 2019, all with level 4/5 evidence.Results The nonunion rate of pediatric scaphoid fractures in the literature is on average 1.5%, occurring mostly as a result of missed or underdiagnosed injuries, similar to our presented case series. Half (n = 9) of the injuries in our case series were missed initial injuries, leading to scaphoid nonunions and half developed nonunions after initial treatment. We found excellent outcomes and with surgical and nonoperative management, with few complications. Not surprisingly, the duration of immobilization is longer with nonoperative management.Conclusions Based on the literature, we recommend a period of nonoperative management before surgery in undisplaced nonunions. In displaced nonunions, open reduction and internal fixation ± bone grafting is necessary. In pediatric scaphoid fractures, similar to adult cases, we identified that suspicious scaphoid fractures should be considered for initial immobilization, and repeat X-rays and early magnetic resonance imaging (MRI) or computed tomography (CT) scans should be considered at follow-up. Immobilization time and type of plaster should be appropriate in relation to the fracture site, similar to the adult scaphoid fracture.Level of Evidence This is a Level IV study.
Keywords: pediatric; scaphoid; nonunion; pseudarthrosis; outcome